Preparation method of novel heat-not-burn high-thermal-conductivity white cigarette thin paper
By adding boron nitride nanofibers and boron nitride floc fibers to cigarette paper, the problem of insufficient thermal conductivity of cigarette paper is solved, more uniform heat transfer and paper strength are achieved, and the need for circumferential heating is met.
Patent Information
- Application Number
- CN202510000930.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-02
- Publication Date
- 2025-03-28
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The thermal conductivity of existing heating-free cigarette papers is insufficient and cannot meet the fast and uniform heat transfer requirements of circumferential heating, resulting in uneven heating tobacco, affecting the consistency of taste and aroma.
By adding boron nitride nanofibers and boron nitride floc fibers to cigarette paper, the thermal conductivity and strength of the paper are improved by utilizing their high thermal conductivity and white powdery properties. Boron nitride nanofibers are evenly dispersed on the surface of the paper through the coating liquid, further enhancing the thermal conductivity.
The thermal conductivity of heating non-combust cigarette paper is significantly improved, more uniform heat transfer is achieved, the strength and breathability of the paper are enhanced, and the needs of circumferential heating are met.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to a preparation method and technology of a novel heat-not-burn high-thermal-conductivity white cigarette paper, belonging to the technical field of pulping and papermaking and heat-not-burn cigarette paper circumferential heating materials. Background Art
[0002] Against the backdrop of the evolving global tobacco industry and the growing public health awareness, the research and development of new tobacco products is of great significance that cannot be ignored. New tobacco products mainly include heat-not-burn cigarettes, e-cigarettes, oral tobacco, snus and other types. At the same time, the pace of global tobacco control actions continues to accelerate, and promoting technological changes and breakthroughs in the tobacco field is of key strategic significance to the survival and development of the tobacco industry under the new global health and policy landscape.
[0003] Among them, heat-not-burn cigarettes occupy a key position in new tobacco products. Through a specific heating method, tobacco releases flavor substances and nicotine in a non-burning state, thereby significantly reducing many harmful components produced during the combustion process of traditional cigarettes, such as tar, carbon monoxide, and various carcinogenic polycyclic aromatic hydrocarbons, providing consumers with a relatively low-harm smoking experience.
[0004] There are two main heating structures for heat-not-burn cigarettes on the market. The first is the central heating structure, and the second is the circumferential heating structure. Central heating has disadvantages such as uneven heating, easy carbonization of the central part of the tobacco, and the carbonized tobacco adhering to the heating needle, causing flavor cross-talk. In the circumferential heating mode, heat is transferred synchronously from the circumferential direction of the cigarette paper to the internal tobacco, so that each radial position of the tobacco can be heated almost synchronously, effectively avoiding the phenomenon that the central part is heated too early and excessively while the surrounding area heats up later, which is easy to occur during central heating. In addition, circumferential heating reduces the loss of heat during the transfer process.
[0005] Existing cigarette paper technology has obvious deficiencies when facing the requirements of circumferential heating. The thermal conductivity of ordinary cigarette paper often cannot meet the requirements of rapid and uniform heat transfer in circumferential heating. It takes a long time for the heat to reach the tobacco sheet and release smoke, which can easily cause uneven heating of the tobacco and affect the consistency of taste and aroma. Reducing consumer experience and product acceptance has hindered the development of heat-not-burn cigarette technology. Therefore, it is urgent to improve the thermal conductivity of heat-not-burn cigarette paper.
[0006] The development of this patent can improve the thermal conductivity of cigarette paper while ensuring the strength of the paper, making it easier to achieve circumferential heating and improving the performance of heat-not-burn cigarette paper. Summary of the invention
[0007] The main purpose of the present invention is to improve the thermal conductivity of heat-not-burn cigarette paper. Based on the research on the performance of cigarette paper, the thermal conductivity of the paper is regulated, such as reducing the thickness of the paper, adding high thermal conductivity materials, etc. From the perspective of fiber characteristics and functional additives, the influence of adding additives on the performance of the paper and the mechanism of action are studied, and the key properties of the cigarette paper such as strength, air permeability and thermal conductivity are comprehensively evaluated. Currently, the commonly used thermal conductive fillers are: aluminum nitride, silicon carbide aluminum oxide, boron nitride, carbon powder and carbon nanotubes, among which carbon nanotubes are the thermal conductive materials with the highest thermal conductivity coefficient, but they are expensive and black in color, which will change the original color of the cigarette paper, and the addition of powdered fillers will cause the strength of the cigarette paper to be greatly reduced. Therefore, this patent improves the strength and thermal conductivity of cigarette paper by preparing boron nitride flocculent fibers and adding them to the papermaking system, overcoming the disadvantage of existing thermally conductive granular fillers that reduce paper strength. At the same time, by preparing a boron nitride nanofiber coating liquid and coating it on the surface of the base paper, the boron nitride nanofibers are further evenly dispersed and filled into the paper fibers and between the fibers, thereby ensuring that the paper surface is uniform, smooth and has a certain strength, while further improving the thermal conductivity of the heat-not-burn cigarette paper.
[0008] In order to achieve the above object, the present invention mainly adopts the following steps: 1. Preparation of boron nitride nanofibers: 40%~60% boric acid is selected as a boron source, 10%~15% ammonium chloride (NH4Cl), 10%~15% hydrazine hydrate (N2H4·H2O), and 20%~30% sodium azide (NaN3) are used as a nitrogen source, and they are mixed with an aqueous solution to form a uniformly mixed reaction system, which is added to a high-pressure reactor and reacted at a reaction temperature of 300~500°C for 24 hours. After cooling to room temperature, the system is filtered and washed, and dried at 60°C to obtain boron nitride nanofibers. The boron nitride nanofibers prepared in the first step are hexagonal boron nitride (H type) with an average particle size of 10~14 μm and are in the form of white powder.
[0009] 2. Preparation of boron nitride flocculent fiber: 40%~60% boric acid is selected as the boron source, 40%~60% melamine is used as the nitrogen source, and the reaction is carried out in a water bath at 95°C for 12 h. After cooling to room temperature, it is filtered and washed, and dried at 60°C to obtain a melamine diboric acid complex, which is then configured into a solution with a concentration of 0.5~0.9 g / L, dissolved at 95°C, cooled to 60°C, and placed in an ultra-low temperature refrigerator at minus 50°C for freezing, and then freeze-dried to obtain a white flocculent sample. The white flocculent sample is placed in a tubular furnace and heated to 1100~1300°C under N2 conditions to finally obtain boron nitride flocculent fiber; the boron nitride flocculent fiber prepared in the second is hexagonal boron nitride (H type), with a diameter of 3~5 μm and a length of 20~40 μm, which is a white flocculent compound.
[0010] 3. Preparation of boron nitride fiber thermal conductive base paper: 8~15% of softwood pulp and 30~50% of hardwood pulp (relative to the paper weight) are mixed evenly, the softwood pulp beating degree is 60~70°SR, the hardwood pulp beating degree is 60~70°SR, and then 0.08~0.12% of pulp dispersant is added, 10%~15% of calcium carbonate is added to the mixed pulp, and stirred evenly, and then 0.1%~0.2% of guar gum retention aid and 4%~10% of guar gum enhancer are added, and after stirring evenly, the dispersed 40~60% boron nitride floccules are added. The boron nitride fiber is added to the prepared original pulp, mixed evenly, and sent to the papermaking system, and then dried and calendered to obtain the boron nitride fiber thermal conductive cigarette base paper; the pulp dispersant described in the third is one or more of potassium oleate, sodium carboxymethyl cellulose and sodium lignin sulfonate, and potassium oleate, sodium carboxymethyl cellulose and sodium lignin sulfonate are all solutions with a mass concentration of 5-10%, wherein the amount of potassium oleate accounts for 0-100% of the total amount of dispersants, the amount of sodium carboxymethyl cellulose accounts for 0-100% of the total amount of dispersants, and the amount of sodium lignin sulfonate accounts for 0-100% of the total amount of dispersants.
[0011] The guar gum enhancer described in the third has a relatively high molecular weight, ranging from millions to tens of millions, and its chemical structure is relatively closer to natural guar gum. The guar gum retention agent has a molecular weight ranging from hundreds of thousands to millions, and has a positive charge on the surface. Both are light yellow powders and are prepared into solutions with a mass concentration of 0.5% to 1%.
[0012] The boron nitride flocculent fibers described in the third are stirred at high speed for 30 minutes in water at 65°C before being added to ensure that they are evenly dispersed in the water, and then added to the original pulp for mixing. The wet paper web is dried at 90-95°C, calendered at 95-105°C, and pressure is 20-40 N / mm 2 .
[0013] 4. Preparation of boron nitride nanofiber coating liquid: Add boron nitride nanofibers into 75°C water and stir at high speed for 30 min to prepare a coating with a concentration of 10%~30%, and then mix it with a starch solution with a concentration of 5%~8% to obtain a boron nitride nanofiber coating liquid.
[0014] The boron nitride nanofibers and starch in the boron nitride nanofiber coating solution described in claim 4 are mixed in a mass ratio of 75:25, 50:50, or 60:40.
[0015] 5. Apply the mixed boron nitride nanofiber coating on the boron nitride fiber thermal conductive cigarette base paper, and then dry it to obtain a new type of heat-not-burn high thermal conductive white cigarette thin paper with a basis weight of 32-38 g / m 2 , coating amount is 2~3 g / m 2The tensile index is 25~28 N·m / g, the air permeability is 15~17 mL / min, and the thermal conductivity can reach 0.15~0.25 W / m·k, which meets the product thermal conductivity standards.
[0016] The drying temperature of the coated paper web described in step 5 is 85°C to 105°C.
[0017] The present invention develops a multi-step and finely controlled boron nitride nanofiber preparation process, adopts a multi-source nitrogen combination, produces a synergistic effect during the hydrothermal reaction, promotes the formation of boron nitride nanofibers, and improves reaction efficiency and product quality.
[0018] The boron nitride flocculent fiber developed in the present invention uses a combined process of water bath reaction, freeze drying and tubular furnace high temperature treatment during the preparation process, and realizes the transformation from raw materials to boron nitride flocculent fibers with specific microstructure and macroscopic morphology through orderly operation of different temperature sections.
[0019] The papermaking additives used in the present invention will not cause harm to human body and environment, meet the environmental protection requirements, and ensure the safety of product use.
[0020] The present invention adopts a method of combining filling and coating of boron nitride fiber materials to effectively solve the problem of insufficient thermal conductivity of heat-not-burn cigarette paper, and at the same time solves the problem of poor paper strength caused by low cigarette paper quantity and more added fillers, effectively avoiding the frequent breakage of cigarette paper during papermaking, and ensuring the smooth progress of the papermaking process. DETAILED DESCRIPTION
[0021] In order to better understand the present invention, the content of the invention is further described below in conjunction with embodiments, but the scope of protection claimed in the present invention is not limited thereto. Example 1
[0022] A method for preparing a novel heat-not-burn high thermal conductivity white cigarette paper, the steps of which are as follows: (1) 60% boric acid, 10% ammonium chloride (NH4Cl), 10% hydrazine hydrate (N2H4·H2O), and 20% sodium azide (NaN3) were mixed with an aqueous solution to form a uniformly mixed reaction system, which was added to a high-pressure reactor and reacted at a reaction temperature of 300°C for 24 h. After cooling to room temperature, the system was filtered and washed, and then dried at 60°C to obtain boron nitride nanofibers. (2) 50% boric acid and 50% melamine were reacted in a water bath at 95°C for 12 h, cooled to room temperature, filtered and washed, dried at 60°C, and then prepared into a solution with a concentration of 0.5 g / L, dissolved at 95°C, cooled to 60°C and placed in an ultra-low temperature refrigerator at -50°C, and then freeze-dried to obtain a white flocculent sample. The white flocculent sample was placed in a tubular furnace and heated to 1200°C under N2 conditions to finally obtain boron nitride flocculent fibers.
[0023] (3) 10% of coniferous wood pulp and 50% of hardwood wood pulp were mixed evenly. The beating degree of coniferous wood pulp was 65°SR and that of hardwood wood pulp was 68°SR. 0.08% potassium oleate was added to the mixed pulp and dispersed evenly. Then 0.2% of guar gum retention aid and 4% of guar gum reinforcement were added. 40% of boron nitride flocculent fiber was put into 100 mL of water and stirred at high speed at 65°C. After the mixture was dispersed evenly, 15% of light calcium carbonate was added to the mixed pulp. After stirring evenly, the mixture was sent to the papermaking system. The wet paper web was dried at 90°C and the pressure was 20 N / mm. 2 , and calendering is performed at a temperature of 95°C to obtain boron nitride fiber thermal conductive base paper.
[0024] (4) The boron nitride nanofibers were prepared into a coating liquid with a mass concentration of 20%, dispersed at high speed at 75°C for 30 min, and mixed with a starch solution with a concentration of 8% in a ratio of 50:50 to obtain a coating. The mixed coating was applied to the boron nitride fiber thermal conductive cigarette base paper, and then dried at 85°C to obtain a new type of heat-not-burn high thermal conductive white cigarette thin paper with a basis weight of 32.76 g / m 2 , coating weight is 2.1 g / m 2 , the tensile index is 25.82 N·m / g, the air permeability is 17 mL / min, and the thermal conductivity can reach 0.18 W / m·k. Example 2
[0025] A method for preparing a novel heat-not-burn high thermal conductivity white cigarette paper, the steps of which are as follows: (1) 40% boric acid, 15% ammonium chloride (NH4Cl), 15% hydrazine hydrate (N2H4·H2O), and 30% sodium azide (NaN3) were mixed with an aqueous solution to form a uniformly mixed reaction system, which was added to a high-pressure reactor and reacted at a reaction temperature of 400°C for 24 h. After cooling to room temperature, the system was filtered and washed, and then dried at 60°C to obtain boron nitride nanofibers. (2) 60% boric acid and 40% melamine were reacted in a water bath at 95°C for 12 h, cooled to room temperature, filtered and washed, dried at 60°C, and then prepared into a solution with a concentration of 0.9 g / L, dissolved at 95°C, cooled to 60°C and placed in an ultra-low temperature refrigerator at -50°C, and then freeze-dried to obtain a white flocculent sample. The white flocculent sample was placed in a tubular furnace and heated to 1100°C under N2 conditions to finally obtain boron nitride flocculent fibers.
[0026] (3) 10% of softwood pulp and 40% of hardwood pulp were mixed evenly. The beating degree of softwood pulp was 60°SR and that of hardwood pulp was 65°SR. 0.1% of dispersant (the dispersant was a mixed solution of 50% potassium oleate and 50% sodium lignin sulfonate) was added to the mixed pulp and dispersed evenly. Then 0.1% of guar gum retention aid and 7% of guar gum reinforcing agent were added. 50% of boron nitride flocculent fiber was put into 100 mL of water and stirred at high speed at 65°C. After it was dispersed evenly, 13% of heavy calcium carbonate was added to the mixed pulp and stirred evenly. After it was sent to the papermaking system, the wet paper web was dried at 93°C and the pressure was 25 N / mm. 2 , and calendering is performed at a temperature of 100°C to obtain boron nitride fiber thermal conductive base paper.
[0027] (4) The boron nitride nanofibers were prepared into a coating liquid with a mass concentration of 25%, dispersed at high speed at 75°C for 30 min, and mixed with a 6% starch solution in a ratio of 60:40 to obtain a coating. The mixed boron nitride nanofiber coating was applied to the boron nitride fiber thermal conductive cigarette base paper, and then dried at 95°C to obtain a new type of heat-not-burn high thermal conductive white cigarette thin paper with a basis weight of 33.53 g / m 2 , coating weight is 2.5 g / m 2 , the tensile index is 26.43 N·m / g, the air permeability is 16mL / min, and the thermal conductivity can reach 0.22 W / m·k. Example 3
[0028] A method for preparing a novel heat-not-burn high thermal conductivity white cigarette paper, the steps of which are as follows: (1) 55% boric acid, 10% ammonium chloride (NH4Cl), 10% hydrazine hydrate (N2H4·H2O), and 25% sodium azide (NaN3) were mixed with an aqueous solution to form a uniformly mixed reaction system, which was added to a high-pressure reactor and reacted at a reaction temperature of 500°C for 24 h. After cooling to room temperature, the system was filtered and washed, and then dried at 60°C to obtain boron nitride nanofibers. (2) 55% boric acid and 45% melamine were reacted in a water bath at 95°C for 12 h, cooled to room temperature, filtered and washed, dried at 60°C, and then prepared into a solution with a concentration of 0.8 g / L, dissolved at 95°C, cooled to 60°C and placed in an ultra-low temperature refrigerator at -50°C, and then freeze-dried to obtain a white flocculent sample. The white flocculent sample was placed in a tubular furnace and heated to 1300°C under N2 conditions to finally obtain boron nitride flocculent fibers.
[0029] (3) 8% of softwood pulp and 30% of hardwood pulp were mixed evenly, with the beating degree of softwood pulp being 70°SR and the beating degree of hardwood pulp being 70°SR. 0.12% of dispersant (the dispersant was a mixed solution of 50% sodium lignin sulfonate and 50% sodium carboxymethyl cellulose) was added to the mixed pulp and dispersed evenly. Then 0.2% of guar gum retention aid and 10% of guar gum reinforcing agent were added. 60% of boron nitride flocculent fiber was put into 100 mL of water and stirred at high speed at 65°C to disperse it evenly. 10% of calcium carbonate mixed filler (mixed with 80% light calcium carbonate and 20% heavy calcium carbonate) was added to the mixed pulp, stirred evenly and sent to the papermaking system. The wet paper web was dried at 95°C with a pressure of 30 N / mm 2 , and calendering is performed at a temperature of 105°C to obtain boron nitride fiber thermal conductive base paper.
[0030] (4) The boron nitride nanofibers were prepared into a coating liquid with a mass concentration of 30%, dispersed at high speed at 75°C for 30 min, and mixed with a 5% starch solution at a concentration of 75:25 to obtain a coating. The mixed boron nitride nanofiber coating was applied to the boron nitride fiber thermal conductive cigarette base paper, and then dried at 105°C to obtain a new type of heat-not-burn high thermal conductive white cigarette thin paper with a basis weight of 34.89 g / m 2 , coating weight is 2.8 g / m 2 , the tensile index is 27.33 N·m / g, the air permeability is 16mL / min, and the thermal conductivity can reach 0.25 W / m·k.
[0031] The performances of the samples of Examples 1, 2 and 3 were compared and analyzed with those of cigarette paper A with thermal conductive filler added and ordinary cigarette paper B without thermal conductive filler added, as shown in Table 1.
[0032] Table 1 is a comparative analysis of the performance of the new heat-not-burn high thermal conductivity white cigarette paper
[0033] The data in Table 1 show that the addition of the boron nitride fibers of Examples 1, 2, and 3 can increase the thermal conductivity of the heat-not-burn cigarette paper by 3 to 5.5 times, and the combination of in-slurry addition and coating of the boron nitride fiber material can effectively solve the problem of a significant decrease in cigarette paper strength caused by the addition of powder fillers.
[0034] The above embodiments are only used to illustrate the present invention but are not limited thereto. It should be understood that there may be many variations and replacement methods without departing from the spirit of the invention.
Claims
1. A method for preparing a novel heat-not-burn high thermal conductivity white cigarette paper, characterized in that: The steps include: (1) Preparation of boron nitride nanofibers: 40% to 60% boric acid is selected as a boron source, 10% to 15% ammonium chloride (NH4Cl), 10% to 15% hydrazine hydrate (N2H4·H2O), and 20% to 30% sodium azide (NaN3) are selected as a nitrogen source, mixed with an aqueous solution to form a uniformly mixed reaction system, added to a high-pressure reactor, reacted at a reaction temperature of 300 to 500°C for 24 h, cooled to room temperature, filtered and washed, and dried at 60°C to obtain boron nitride nanofibers; (2) Preparation of boron nitride flocculent fibers: 40% to 60% boric acid was selected as the boron source and 40% to 60% melamine was used as the nitrogen source. The mixture was reacted in a water bath at 95°C for 12 h. After cooling to room temperature, the mixture was filtered and washed, and then dried at 60°C to obtain a melamine diboric acid complex. The complex was then prepared into a solution with a concentration of 0.5 to 0.9 g / L, dissolved at 95°C, cooled to 60°C, and then placed in an ultra-low temperature refrigerator at -50°C. The complex was then freeze-dried to obtain a white flocculent sample. The white flocculent sample was placed in a tubular furnace and heated to 1100 to 1300°C under N2 conditions to obtain boron nitride flocculent fibers. (3) 8-15% of softwood pulp and 30-50% of hardwood pulp (relative to the paper weight) are mixed evenly, the softwood pulp has a beating degree of 60-70°SR, and the hardwood pulp has a beating degree of 60-70°SR, and then 0.08-0.12% of a pulp dispersant is added, 10%-15% of calcium carbonate is added to the mixed pulp, and the mixture is stirred evenly, and then 0.1%-0.2% of a guar gum retention aid and 4%-10% of a guar gum enhancer are added, and after stirring evenly, 40-60% of the dispersed boron nitride flocculent fibers are added to the prepared raw pulp, mixed evenly, and fed into a papermaking system, and then dried and calendered to obtain a boron nitride fiber thermal conductive cigarette base paper; (4) Preparation of boron nitride nanofiber coating liquid: Add boron nitride nanofibers into 75°C water and stir at high speed for 30 min to prepare a coating with a concentration of 10% to 30%, and then mix it with a starch solution with a concentration of 5% to 8% to obtain a boron nitride nanofiber coating liquid; (5) The mixed boron nitride nanofiber coating is applied to the boron nitride fiber thermal conductive cigarette base paper, and then dried to obtain the boron nitride fiber thermal conductive cigarette thin paper, the basis weight of which is 32-38 g / m 2 , coating amount is 2~3 g / m 2 The tensile index is 25~28N·m / g, the air permeability is 15~17 mL / min, and the thermal conductivity can reach 0.15~0.25 W / m·k, which meets the product thermal conductivity standards.
2. The method for preparing a novel heat-not-burn high thermal conductivity white cigarette thin paper according to claim 1 is characterized in that: The boron nitride nanofibers prepared in step (1) are hexagonal boron nitride (H-type) with an average particle size of 10-14 μm and in the form of white powder.
3. The method for preparing a novel heat-not-burn high thermal conductivity white cigarette thin paper according to claim 1 is characterized in that: The boron nitride flocculent fiber prepared in step (2) is hexagonal boron nitride (H-type), has a diameter of 3-5 μm, a length of 20-40 μm, and is a white flocculent compound.
4. The method for preparing a novel heat-not-burn high thermal conductivity white cigarette paper according to claim 1 is characterized in that: The slurry dispersant in step (3) is one or more of potassium oleate, sodium carboxymethyl cellulose and sodium lignin sulfonate, wherein potassium oleate, sodium carboxymethyl cellulose and sodium lignin sulfonate are all solutions with a mass concentration of 5-10%, wherein the amount of potassium oleate accounts for 0-100% of the total amount of dispersant, the amount of sodium carboxymethyl cellulose accounts for 0-100% of the total amount of dispersant, and the amount of sodium lignin sulfonate accounts for 0-100% of the total amount of dispersant.
5. The method for preparing a novel heat-not-burn high thermal conductivity white cigarette paper according to claim 1 is characterized in that: The calcium carbonate particles in step (3) are one or both of light calcium carbonate and heavy calcium carbonate, the average particle size of light calcium carbonate is in the range of 0.5-3 μm, and the average particle size of heavy calcium carbonate is in the range of 6-9 μm, wherein the amount of light calcium carbonate accounts for 0-100% of the total amount of calcium carbonate, and the amount of heavy calcium carbonate accounts for 0-100% of the total amount of calcium carbonate.
6. The method for preparing a novel heat-not-burn high thermal conductivity white cigarette paper according to claim 1 is characterized in that: The guar gum enhancer described in step (3) has a relatively high molecular weight, ranging from millions to tens of millions, and its chemical structure is relatively closer to natural guar gum. The guar gum retention agent has a molecular weight ranging from hundreds of thousands to millions, and has a positive charge on its surface. Both are light yellow powders. The guar gum retention agent and the guar gum enhancer are prepared into a solution with a mass concentration of 0.5% to 1%.
7. The method for preparing a novel heat-not-burn high thermal conductivity white cigarette paper according to claim 1 is characterized in that: The boron nitride flocculent fibers described in step (3) are stirred at high speed for 30 minutes in water at 65°C before being added to ensure that they are evenly dispersed in the water, and then added to the original pulp for mixing. The wet paper web is dried at a temperature of 90-95°C, calendered at a temperature of 95-105°C, and pressure of 20-40 N / mm 2 .
8. The method for preparing a novel heat-not-burn high thermal conductivity white cigarette paper according to claim 1 is characterized in that: The boron nitride nanofibers and starch in the boron nitride nanofiber coating solution of step (4) are mixed in a mass ratio of 75:25, 50:50, or 60:
40.
9. The method for preparing a novel heat-not-burn high thermal conductivity white cigarette paper according to claim 1 is characterized in that: The drying temperature of the coated paper web in step (5) is 85°C to 105°C.
Citation Information
Patent Citations
Preparation method of porous boron nitride nanofibers
CN104528671A
Preparation method of heat-not-burn cigarette paper containing boron nitride heat-conducting filler
CN113152145A
Heat-conducting insulation paper and preparation method thereof
CN115595819A
Heat-insulating and flame-retardant boron nitride-based aerogel and preparation method thereof
CN117487255A